Schistura maejotigrina, a new stream loach (Pisces: Nemacheilidae) from northern Thailand - Suvarnaraksha, Apinun (Zootaxa, 2012)
Schistura maejotigrina, new species, is described from Maechaem River, a tributary of Ping River, in the upper Chao Phra-ya River drainage, Chiang Mai Province, Thailand. It is distinguished from all other species of Schistura in having 21–24dark tiger-stripe black bars on the side of the body and 6½–7½ branched dorsal soft rays. The species is medium-sized,reaching 53.0 mm SL (69.6 mm TL), and is known only from the Maechaem River system, Ping River drainage, northernChao Phraya River basin, Chiang Mai Province, Thailand. It lives in fast running, clear water over a substrate of mixed gravel, small stone and sand.